Analysis of Human Resource Management, Interpersonal Communication and Internal Control on the Effectiveness of Health Services at Rsud Prov South Sumatra - Paramitha Sari Dwi Saputri; Azwardi Azwardi; Ika Sasti Ferina (UNIVED Press, 2023)
This study aims to obtain empirical evidence about the analysis of human resource management, interpersonal communication and internal control on the effectiveness of health services at the South Sumatra Prov Hospital. This study used mix method. Research results Overall the variable of human resource management with an average percentage of 80.43%, which means that the human resource management in the is very good at carrying out its duties. Second, interpersonal communication with an average percentage of 83.34%, which means that communication in the is running very well, be it between employees or direct communication with superiors. Internal control with an average percentage of 84.42%, which means that everything is going well and is in accordance with existing SOPs. Then, the effectiveness of health services obtained an average percentage of 85.88%, which means that the services provided have been carried out as optimally the South Sumatra Prov Hospital.